Household food waste: Drivers and potential intervention points for design – An extensive review. (10th May 2017) - Hebrok, Marie; Boks, Casper
Abstract: This review describes the consumer related material and socio-cultural drivers behind food waste found in academic and grey literature. The aim is to identify intervention points for design interventions to reduce household food waste. Within the reviewed literature, an array of different aspects of consumer food waste is studied such as consumer behaviour, attitudes, beliefs and values, quantifications and compositional analyses of food waste in Western countries, waste prevention and concrete design interventions. This illustrates that the problem of consumer food wasting practices is an issue that is complex and involves both socio-cultural and material factors. However, the literature is more focused on generating knowledge about the problem than on finding solutions. Thus, further research should attempt to find ways to test new ideas and interventions that could reduce food waste in households.